Thermal Stability of Filtered Vacuum Arc Deposited Er2O3 Coatings - Zukerman, I.; Goldenberg, E.; Zhitomirsky, V.N.; Raveh, A.; Boxman, R.L. (Journal of Coating Science and Technology, 2015)
Erbium oxide (Er2O3) coatings were deposited using filtered vacuum arc deposition (FVAD) and their structure and thermal stability were studied as a function of fabrication parameters. The coatings were deposited on silicon wafer and tantalum substrates with an arc current of 50 A and a deposition rate of 1.6 ± 0.4 nm/s. The arc was sustained on truncated cone Er cathodes. The influence of oxygen pressure (P= 0.40-0.93 Pa), bias voltage (Vb= -20, -40 or grounded) and substrate temperature (room temperature (RT) or 673K) on film properties was studied before and after post deposition annealing (1273K for 1 hour, at P~ 1.33 Pa). The coatings were characterized using X-ray diffraction (XRD), optical microscopy, scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and Knoop Hardness. Optical microscope images indicated that the coatings had very low macroparticle concentration on their surface. The macroparticle diameters were less than 2.5 μm. The coatings were composed of only Er2O3 without any metallic phase under all deposition parameters tested. The coatings deposited on RT substrates were XRD amorphous and had a featureless cross-section microstructure. However, the coatings deposited on 673K heated substrates had a C-Er2O3 structure with (222) preferred orientation and weak columnar microstructure. The coating hardness varied with deposition pressure and substrate bias, and reached a maximum value of 10 GPa at P = 0.4 Pa and Vb = -40 V. The post-deposition annealing caused crystallization, and the coatings hardness dropped to 4 GPa with thermal treatment. However, after post-deposition annealing, no peeling or cracking appeared at the coating surface or the interface with the substrate.